Tauopathy in basal ganglia involvement is exacerbated in a subset of patients with Alzheimer's disease: The Hisayama study. Issue 1 (6th June 2019) - Hamasaki, Hideomi; Honda, Hiroyuki; Suzuki, Satoshi O.; Shijo, Masahiro; Ohara, Tomoyuki; Hatabe, Yozo; Okamoto, Tsuyoshi; Ninomiya, Toshiharu; Iwaki, Toru
Abstract: Introduction: We have conducted the pathological cohort study of autopsied cases of Hisayama residents to reveal a recent trend of dementia‐related pathology. We noticed a trend of putaminal involvement of Alzheimer's disease (AD) with parkinsonism. Then, we investigated the accurate prevalence of neurological diseases with putaminal AD pathology in the general population. Methods: We examined a series of 291 autopsies in the Hisayama study and performed image analysis of immunohistochemistry for microtubule‐associated protein tau (MAPT) and amyloid β. Results: Approximately 65.6% and 36.1% of cases showed putaminal MAPT and amyloid deposits, respectively. Diffuse deposits of them were mainly found in the AD cases. Putaminal MAPT was highly associated with AD‐related pathological criteria. Four of 22 cases with severe putaminal MAPT deposition were documented as having developed parkinsonism. Discussion: Severe MAPT accumulation in the basal ganglia was closely related to the development of AD pathology and could occur most frequently in AD cases without comorbidities.